2022
DOI: 10.1002/csr.2360
|View full text |Cite
|
Sign up to set email alerts
|

Green human resource management, a gateway to employer branding: Mediating role of corporate environmental sustainability and corporate social sustainability

Abstract: This study proposes a model based on competitive advantage and signaling theories that show how green human resource management (GHRM) leads to corporate environmental sustainability and corporate social sustainability and is thus source of employer branding. Structural equational modeling was used for data analysis through Smart PLS. The results confirm that GHRM positively influences on corporate environmental sustainability, which in turn positively influences corporate social sustainability. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 104 publications
2
43
0
1
Order By: Relevance
“…Although a company's environmental ethics have an ideological effect on employees' commitment toward the environment, sustainable HRM formalizes a company's environmental ethics through the adoption of a different environmental policy (Ahmed et al, 1998; Guo et al, 2020; Han et al, 2019). Therefore, sustainable HRM and enterprise environmental ethics form a natural alliance or match, and jointly help enterprises realize the sustainable development of both environment and society (Yasin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a company's environmental ethics have an ideological effect on employees' commitment toward the environment, sustainable HRM formalizes a company's environmental ethics through the adoption of a different environmental policy (Ahmed et al, 1998; Guo et al, 2020; Han et al, 2019). Therefore, sustainable HRM and enterprise environmental ethics form a natural alliance or match, and jointly help enterprises realize the sustainable development of both environment and society (Yasin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sustainable HRM and enterprise environmental ethics form a natural alliance or match, and jointly help enterprises realize the sustainable development of both environment and society (Yasin et al, 2023).…”
Section: Contributions To Theorymentioning
confidence: 99%
“…Another empirical study confirmed that GHRM influenced bank employees’ green behaviors through green commitment (Khan et al , 2022). Moreover, GHRM triggered environmental sustainability which in turn influenced corporate social responsibility and employee branding in the textile sector (Yasin et al , 2022). It was reported that the environmental beliefs of Chinese companies’ chief executive officers were positively linked to GHRM practices which in turn resulted in better environmental and financial performances via employees’ environmental commitment (Ren et al , 2022).…”
Section: Literature Review Hypotheses and Research Modelmentioning
confidence: 99%
“…Firms report their practice, which should reflect stakeholders' concerns and demands (Montiel, 2008; Perrini & Tencati, 2006). This reflection leads us to understand that environmental and social corporate matters are significant for business economic development (Li et al, 2020; Yasin et al, 2022). Concerning environmental issues, the focus of this research, recent studies discuss the influences of corporate environmental management on the competitive sustainability of organizations (Dzeraviaha, 2022; Li et al, 2020; Yasin et al, 2022).…”
Section: Theoretical Reasoningmentioning
confidence: 99%